2019
DOI: 10.15252/emmm.201910769
|View full text |Cite
|
Sign up to set email alerts
|

Activation of LXR β inhibits tumor respiration and is synthetically lethal with Bcl‐ xL inhibition

Abstract: Liver‐X‐receptor (LXR) agonists are known to bear anti‐tumor activity. However, their efficacy is limited and additional insights regarding the underlying mechanism are necessary. By performing transcriptome analysis coupled with global polar metabolite screening, we show that LXR agonists, LXR623 and GW3965, enhance synergistically the anti‐proliferative effect of BH3 mimetics in solid tumor malignancies, which is predominantly mediated by cell death with features of apoptosis and is rescued by exogenous chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 51 publications
2
23
1
Order By: Relevance
“…A limitation of the current work is that our studies did not include orthotopic in vivo studies, given that the microenvironment and the blood brain barrier might interfere with the efficacy of the treatment. These results are in keeping with earlier drug combinations involving BH3-mimetics [ 7 , 9 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A limitation of the current work is that our studies did not include orthotopic in vivo studies, given that the microenvironment and the blood brain barrier might interfere with the efficacy of the treatment. These results are in keeping with earlier drug combinations involving BH3-mimetics [ 7 , 9 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…Given the limited cell death induction by THZ1, we asked whether the killing efficacy of this compound might be enhanced in the presence of BH3-mimetics, such as ABT263. This hypothesis largely emerged from the fact that THZ1 suppressed Mcl-1 protein levels and that drugs that lower Mcl-1 levels have commonly been associated to enhance the efficacy of BH3-mimetics that target either Bcl-2, Bcl-xL, or both [ 7 , 9 , 42 , 43 , 44 , 45 , 46 ]. Consistently, we found that THZ1 and BH3-mimetics synergistically reduced the viability of GBM cells across a broad range of different model systems of human GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Although our experiments did not directly connect these two phenomena, previous work by us and others has demonstrated a tight linkage between energy deprivation (here mediated by dual loss of the major energetic pathways) and the activation of the integrated stress response [ 36 ]. In part, loss of ATP is linked due to accumulation of unfolded proteins given that proper maturation and protein synthesis depend on an appropriate state of energy within cells and altering this rheostat will affect the integrity of tumor cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…LXR agonists represent novel means to counteract cholesterol levels in tumor cells, including glioblastoma and melanoma, by enhancing the excretion (increase in ABCA1) and, at the same time, by decreasing the resorption of cholesterol (decrease in LDL receptor) ( 121 ). Since LXR agonists upregulate the expression of the pro-apoptotic Bcl-2 family member, Noxa, BH3 mimetics (ABT263 and ABT199), and LXR agonists synergistically reduce cellular viability by enhancing apoptosis, resulting in a synergistic anti-proliferative effect across solid tumor cells ( 121 ).…”
Section: Therapeutic Targets For Cancer Treatmentmentioning
confidence: 99%
“…LXR agonists represent novel means to counteract cholesterol levels in tumor cells, including glioblastoma and melanoma, by enhancing the excretion (increase in ABCA1) and, at the same time, by decreasing the resorption of cholesterol (decrease in LDL receptor) ( 121 ). Since LXR agonists upregulate the expression of the pro-apoptotic Bcl-2 family member, Noxa, BH3 mimetics (ABT263 and ABT199), and LXR agonists synergistically reduce cellular viability by enhancing apoptosis, resulting in a synergistic anti-proliferative effect across solid tumor cells ( 121 ). In preclinical models of diffuse intrinsic pontine glioma, a small molecule, menin inhibitor MI-2, has been proven to disrupt cholesterol homeostasis by inhibiting the conversion of 2,3-oxidosqualene to lanosterol, which also activates LXR to increase cholesterol efflux ( 136 ).…”
Section: Therapeutic Targets For Cancer Treatmentmentioning
confidence: 99%